Digital monitoring of small-scale fisheries in Timor-Leste: An impact assessment - Dam Lam, Rodolfo; Dos Reis Lopes, Joctan; Lozano, Denise; Da Costa, Delia; Belo, Maria; Da Silva, Joaquina; Da Cruz, Gilberto; Tilley, Alexander (WorldFish, 2022)
Digital tools and technologies are transforming the way we monitor and manage food systems and natural resources, but to date there is scant credible collection and analysis of evidence of their impacts on well-being, environmental sustainability, and broader goods and services. The development of information communication technology (ICT) has a crucial role to play in the timely provision of information to guide management and investment decisions by small-scale fisheries (SSF) stakeholders, from coastal fishers to government officials. The implementation of PeskAAS in Timor-Leste is one such attempt. We sought to co-design and roll out a system to collect and analyze fisheries data in near real-time with the aim to (1) strengthen sustainable fisheries resource management in Timor-Leste, (2) promote improved collaboration and communication between fisheries stakeholders, and (3) identify new opportunities to enhance fish-based livelihoods and food systems transformation in the country. This study aimed to assess the progress made toward these goals since 2016 through different pathways since the establishment and iterative development of PeskAAS. Using targeted interviews, we undertook a survey of respondents in key stakeholder groups: fishers, community enumerators, the private sector, nongovernmental organizations (NGOs) and external agencies, municipal fisheries officers and the national government.